Islam and Contemporary Western Thought: Islam and Postmodernism (American Journal of Islam and Society, 1996)
The two books recently authored by Ernest Gellner and Akbar Ahmedon the subject of Islam and postrnodernism have attracted interest amongMuslims and non-Muslims. To me, it is a landmark in the continuing dialoguebetween Islam and the West. Has the rise of postmodernism in westernphilosophical thought meant an easier accommodation of Islam into contemporarywestern society, or is Islam intellectually at odds with the epistemologicalfoundations of postmodernism? These are some of the importantquestions addressed by Gellner and Ahmed. In view of the increasing culturaland intellectual globalization, not to mention the economic side, takingplace today, the place of Islam in contemporary thought and society can nolonger be safely isolated from "western" thought and culture.Unlike previous encounters, where victory was decided through militaryconfrontations, or in times of peace, where coexistence is maintainedthrough the separation of borders limiting influence and interaction, ours isa time when cultures and civilizations are interlocked. Hence, it is of theutmost importance that Muslims define their thought and philosophical positiondearly in relation to the West, if they insist on maintaining their identityand way of life in a world that is increasingly westernized. Part of theMuslim ummah's legitimacy derives from the sovereignty of its individualnations existing in the world community and from the intellectual strengthof its religious and philosophical position. Muslims cannot compromise onthat if they are to maintain their viability as an ummah in the contemporaryworld. Recent intellectual dialogues on Islam and the West, therefore,should acquire an important place in the Musim minds and agenda if theyare not to witness the further erosion of Islamic values and beliefs.In view of the importance of the discussions on Islam by Gellner andAhmed in their recent works, I now tum to an analysis of their books.Gellner on Islam, Rationalism, and PostmodernismAs opposed to previous binary polarities in history, Gellner believes thatour time is characterized by a competition between three irreducible ...